Psychological Impact of COVID 19 Pandemic on Mental Health of Children Admitted to a Tertiary Care Centre - Xavier, Rose; Ravindran, Sreya (Journal of College of Medical Sciences-Nepal, 2024)
Background To prevent the COVID 19 transmission and reduce the burden on health systems, schools were closed and classes shifted to home-based distance learning models with online learning activities. Being quarantined in homes caused great psychological burden to children. This study was done to study the impact of COVID 19 on mental health of children and their screen and sleep behaviour before and during the pandemic. Methods Admitted children aged between 4-14 years and their siblings of same age group were enrolled after getting informed consent from their parents. The information regarding their socio-demographic factors, screen time, sleep time, physical activity and psychological problems were assessed using Paediatric symptom checklist Questionnaire. Outcome was measured by the scores obtained according to their age. Screen time and sleep behaviour was assessed using the guidelines proposed by American Academy of Paediatrics. Results Twenty-seven (15.81%) of 171 children had psychological impairment. The 11–14-year-olds and children living in urban area were more affected. All participants had abnormal screen time with respect to their age during COVID 19 pandemic and 99.4 % had increased screen time compared to pre COVID era. Abnormal sleep pattern was seen in 26.9 % and compared with pre-Covid times 73.6 % of the participants had less physical activity. Conclusions Implementation of psychosocial intervention and lifestyle modification strategies at community level is the need of the hour. Post Covid era remnant and sequalae of psychological impairment needs to be assessed.